Memory and Historiography of the Portuguese Revolution of 1820 - Araújo, Ana Cristina (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
Different manifestations of adherence and rejection and successive times of exaltation and oblivion, both assumed throughout the ages by different groups, individuals and institutions, contributed to fix the historical memory of the 1820 revolution. From the mid-20th century onwards, consistent readings and interpretations of the Portuguese liberal triennium (1820-1823) accentuated the complexity of the historiographical field. With differentiated approaches, historiography broke with old paradigms of interpretation, namely those of the liberal and republican tradition, and with the Marxist-inspired notion of bourgeois revolution applied to the emergence of liberalism. The most recent studies have sought to highlight the Iberian and Atlantic connections of the revolutionary conjuncture. The importance of the Constitution of 1822 for Portuguese political and institutional history in the 19th century has been studied in conjunction with the counter-revolutionary reaction that began in 1823 and the subsequent triumph of Chartist constitutionalism. From a global perspective, the focus on the emergence of an international liberal movement in the post-Napoleonic era has contributed to the study of the connections between the revolutions in Southern Europe.